2002
DOI: 10.1126/science.1069958
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Bi 3.25 La 0.75 Ti 3 O 12 Films of Uniform a -Axis Orientation on Silicon Substrates

Abstract: The use of bismuth-layered perovskite films for planar-type nonvolatile ferroelectric random-access memories requires films with spontaneous polarization normal to the plane of growth. Epitaxially twinned a axis-oriented La-substituted Bi4Ti3O12 (BLT) thin films whose spontaneous polarization is entirely along the film normal were grown by pulsed laser deposition on yttria-stabilized zirconia-buffered Si(100) substrates using SrRuO3 as bottom electrodes. Even though the (118) orientation competes with the (100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
236
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 540 publications
(244 citation statements)
references
References 26 publications
8
236
0
Order By: Relevance
“…The well-defined thickness fringes observed for most of the peaks in θ-2θ patterns together with very narrow full width at half maxima (∆w ~0.025°) in rocking curve scans indicate an atomically smooth surface and interface as well as excellent crystallinity of our thin films. (Note that the full width at half maxima in XRD rocking curves in our films reported here is drastically reduced at least by a factor of three as compared with the values from previous epitaxial films 20 .) Overall peak positions of the main peaks remain unchanged for all the samples up to 1B2L, indicating that the overall Aurivillius structure of BiT is well preserved even after the substitution.…”
Section: Resultssupporting
confidence: 49%
See 2 more Smart Citations
“…The well-defined thickness fringes observed for most of the peaks in θ-2θ patterns together with very narrow full width at half maxima (∆w ~0.025°) in rocking curve scans indicate an atomically smooth surface and interface as well as excellent crystallinity of our thin films. (Note that the full width at half maxima in XRD rocking curves in our films reported here is drastically reduced at least by a factor of three as compared with the values from previous epitaxial films 20 .) Overall peak positions of the main peaks remain unchanged for all the samples up to 1B2L, indicating that the overall Aurivillius structure of BiT is well preserved even after the substitution.…”
Section: Resultssupporting
confidence: 49%
“…The polarization in such non-c-axis-oriented thin films is aligned away from the film plane, so that the ferroelectric measurement can readily be performed in capacitor geometry 20 . Pt top electrodes (30-µm diameter) were deposited on the film surfaces using photolithographic lift-off to fabricate capacitors.…”
Section: Ferroelectric Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…1B). The crystal growth in the a and b axes is related to the intensity of the (117) (36,37). It was also reported that BLT thin film grown epitaxially in the a axis shows a P s value of 50 Ccm Ϫ2 (39).…”
Section: Resultsmentioning
confidence: 93%
“…The combination of good chemical stability, metallic conductivity and easy epitaxial growth on various perovskite substrates makes it attractive for multilayer device application (Lee et al, 2002;Eom et al, 1992;Mercurio et al, 2000). The integrability of SrRuO 3 into the device fabrication process requires surface stability with respect to reduction, contamination, or loss of volatile ruthenium oxides.…”
Section: Introductionmentioning
confidence: 99%